Biomaterial-assisted local oxygenation safeguards the prostimulatory phenotype and functions of human dendritic cells in hypoxia - Bhatt, Khushbu; Nukovic, Alexandra; Colombani, Thibault; Bencherif, Sidi A. (Frontiers in Immunology, 2023)
Dendritic cells (DCs), professional antigen-presenting cells, function as sentinels of the immune system. DCs initiate and fine-tune adaptive immune responses by presenting antigenic peptides to B and T lymphocytes to mount an effective immune response against cancer and pathogens. However, hypoxia, a condition characterized by low oxygen (O2) tension in different tissues, significantly impacts DC functions, including antigen uptake, activation and maturation, migration, as well as Tcell priming and proliferation. In this study, we employed O2-releasing biomaterials (O2-cryogels) to study the effect of localized O2 supply on human DC phenotype and functions. Our results indicate that O2-cryogels effectively mitigate DC exposure to hypoxia under hypoxic conditions. Additionally, O2-cryogels counteract hypoxia-induced inhibition of antigen uptake and migratory activity in DCs through O2 release and hyaluronic acid (HA) mediated mechanisms. Furthermore, O2-cryogels preserve and restore DC maturation and co-stimulation markers, including HLA-DR, CD86, and CD40, along with the secretion of proinflammatory cytokines in hypoxic conditions. Finally, our findings demonstrate that the supplemental O2 released from the cryogels preserves DC-mediated Tcell priming, ultimately leading to the activation and proliferation of allogeneic CD3+ T cells. This work emphasizes the potential of local oxygenation as a powerful immunomodulatory agent to improve DC activation and functions in hypoxia, offering new approaches for cancer and infectious disease treatments.